Pengaruh Pretreatment Batang Sawit Terhadap Sifat Dan Morfologi Wood Plastic Composite (WPC) - Muchlis Ade Putra; Ahmad Fadli; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Palm trunk wood is one of solid waste from palm plantations that have not been utilized optimally. This waste can be developed as materials for Wood Plastic Composite (WPC). Extractive substances and hemicellulose fraction of this material may inhibit mixing process between wood filler and matrix, so it takes a pretreatment to eliminate these fraction. Effect of pretreatment on the properties and morphology of the resulting WPC studied in this research. Pretreatment was performed in an autoclave using water and solution of oxalic acid (OA) with concentration 0,05 M and 0,1 M at soaking temperature 1000C and 1400C then held for 5 and 15 minutes. Mixing the filler and matrix with the ratio 30/70, 2% mass paraffin and 5% mass of Maleic Anhydrate Polypropylene (MAPP) was conducted on Internal Mixer Labo Plastomills with temperature and rotor speed conditions 170 0C and 80 rpm respectively. Results of the lignocellulose analysis showed that highest reduction of extractive substances and hemicellulose fraction was 95,94 % and 25,22 %. The best mechanical and physical properties found in the pretreated sample with conditions 0,05 M OA concentration, 140 0C soaking temperature, and 15 minutes soaking time. The tensile strength, flexural strength, and water absorption values was 273,244 kgf/cm2, 427,551 kgf/cm2 and 1,120 %, respectively.Keywords : filler, lignocelluloce, pretreatment, wood plastic composite